Perumusan Strategi Pemasaran Hijau Kerajinan Rotan untuk Meningkatkan Kepuasan dan Loyalitas Konsumen - Prima Ditahardiyani; Hartoni Hartoni; Redhana Aulia (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The application of the green marketing concept is needed for green product manufacturers to compete and emphasize their competitive advantages effectively. Green marketing offers many benefits to producers, including improved profitability, productivity, and company image. As producers of green products, rattan craft Small and Medium Enterprises should implement green marketing to get more benefits. Nevertheless, rattan craft small and medium-sized enterprises (SMEs) still need to adopt this practice. The lack of ability to effectively convey an environmentally friendly image has led to a decline in consumer satisfaction and loyalty. Therefore, this study aims to formulate a green marketing strategy to enhance consumer satisfaction and loyalty towards rattan handicrafts. The research is located in Banjarbaru City, South Kalimantan Province. Data was collected through in-depth interviews and questionnaires. A green marketing strategy was formulated using the 7P green marketing mix consisting of product, price, place, promotion, people, process and physical evidence and analyzed using Strengths, Weaknesses, Opportunities and Threats (SWOT). The prioritization of green marketing strategy is determined using the Analytical Hierarchy Process (AHP) method. The result indicated that among strengths and opportunities, it is made from materials that are safe for the environment and can be developed into various products are the two most important factors. In contrast, among weaknesses and threats, products are less varied, and the existence of substitute goods such as plastic and bamboo are the weaknesses and threats that are most concern. The alternative green marketing mix strategy formulated consists of maximizing the use of e-commerce, expanding cooperation and networking with stakeholders, increasing innovation and product variants, green advertising in digital media, guaranteeing green products through green label certification, and increasing discounts and bonuses for purchasing a certain amount. The research results also showed that the primary priority strategy is increasing innovation and product variants, while less priority is adding discounts and bonuses for purchasing specific quantities.